2011
DOI: 10.1007/s10955-011-0171-5
|View full text |Cite
|
Sign up to set email alerts
|

Markov Properties of Electrical Discharge Current Fluctuations in Plasma

Abstract: Using the Markovian method, we study the stochastic nature of electrical discharge current fluctuations in the Helium plasma. Sinusoidal trends are extracted from the data set by the Fourier-Detrended Fluctuation analysis and consequently cleaned data is retrieved. We determine the Markov time scale of the detrended data set by using likelihood analysis. We also estimate the Kramers-Moyal's coefficients of the discharge current fluctuations and derive the corresponding Fokker-Planck equation. In addition, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…It has been used to obtain information on the transport coefficients in glow discharges from the time and space autocorrelation function and their corresponding auto-power spectrum of random fluctuations in plasmas [30]. Moreover, it has been shown experimentally that the random current fluctuations exhibit, under certain conditions, the Markovian property in the fully developed turbulence regime [31].…”
Section: Plasma Dynamics As a Stochastic Processmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used to obtain information on the transport coefficients in glow discharges from the time and space autocorrelation function and their corresponding auto-power spectrum of random fluctuations in plasmas [30]. Moreover, it has been shown experimentally that the random current fluctuations exhibit, under certain conditions, the Markovian property in the fully developed turbulence regime [31].…”
Section: Plasma Dynamics As a Stochastic Processmentioning
confidence: 99%
“…Another approach based on the Markovian method can be seen in Ref. [31]. Within the first formalism, it is shown that fluctuating phenomena which are described by dynamical equations having the GENERIC structure are stationary, Gaussian, and Markovian processes.…”
Section: Fm Model For Fluctuations In Glow Dischargesmentioning
confidence: 99%
“…2(c). Observables of high-dimensional chaotic systems, such as isotropic turbulence [51], solar winds [52], electrical discharge fluctuation [53], and gel transitions [54], can be quantitatively indistinguishable from those of a stochastic system. Thus, given the difficulty of reconstructing the high-dimensional attractor, such systems have sometimes been modeled as stochastic processes.…”
Section: Introductionmentioning
confidence: 99%